Profile of intoxications served at the 24-hour emergency service unit - Ana Carolina Arrebola Tredice Di Palma; Thaís Lorenna Souza Sales; Geisa Cristina Silva Alves; Sayonara Maria Lia Fook; Alba Otoni; Cristina Sanches; Farah Maria Drumond Chequer (São Paulo State University (UNESP), 2020)
Intoxications represent a serious public health problem. According to the World Health Organization, 193,000 deaths per year are caused by unintended intoxications worldwide. This study aims to know the profile of intoxications at the 24-hour Emergency Service Unit in Divinópolis, in the state of Minas Gerais. This is a descriptive study in which the study population chosen were all patients treated for intoxications in the period from 2017 to 2018, registered in the health service; 421 cases of intoxications were recorded. The female gender was the most prevalent, and the age group with the most cases was 21 to 30 years. The main circumstance found was attempted suicide (83.1 %), and the main causative agent was medication (76.5 %), with benzodiazepines being the main class responsible for intoxications. The most used treatment was gastric lavage and activated charcoal. This study demonstrates that knowledge about the city's intoxication profile is important for the development of treatment and patient management methods to better suit the demands of the municipality.